Dissimilar materials joining of metal/carbon fibre reinforced plastic by resistance spot welding. Issue 7 (3rd July 2018) - Nagatsuka, Kimiaki; Xiao, Bolyu; Wu, Lihui; Natata, Kazuhiro; Saeki, Shuhei; Kitamoto, Yamato; Iwamoto, Yoshiaki
ABSTRACT: Dissimilar materials joining of metal to carbon fibre reinforced plastic (CFRP), which consisted of PA6, modified polypropylene (PP) or polyphenylene sulphide (PPS) as matrix polymer with short carbon fibre, was performed using series resistance spot welding (series-RSW). The metal plate was placed on CFRP plate as the lap joint, and electrodes of series-RSW were pressed only on the metal plate side. The metal around the electrode was heated by electrical resistance heating, and the thermoplastic near the interface was slightly melted by the heat conduction from heated metal. The objectives of this research are to confirm the possibility of direct joining of CFRP and metal, and to investigate the effects of the heat input during series-RSW, silane-coupling treatment and chemical structure of matrix plastics on the joint properties. The direct joint formations of SUS304 to CFRP (PA6) and CFRP (PP) were accomplished, and CFRP (PPS) was not. The joining area, which corresponding to the melted area of CFRP, enlarged with increasing the welding current and welding time, therefore, the tensile shear fracture load also increased. The silane-coupling treatment for metal surface was highly effective to increase the joining strength. The maximum tensile shear strength of about 13 MPa was obtained for SUS304/CFRP (PA6) joint.